Islamic Esoteric Education in Internalizing Cultural Values of Kampung Keputihan in the Modern Era - Badrudin, Badrudin; Hidayat, Sandra Taufik; Marlina, Yuli; Samrin, Samrin; Nurochim, Nurochim; Wijaya, Candra (Jurnal Ilmiah Peuradeun, 2025)
This article investigated the enduring value of esoteric wisdom in guiding spiritual seekers through contemporary challenges. Despite the fast-paced, chaotic nature of modern life, esoteric teachings offer critical solutions to existential issues that transcend cultural and historical boundaries. Employing a constructivist paradigm qualitative approach, the research aimed to understand individuals’ behaviors, perceptions, motivations, and actions. It revealed how these teachings aid in achieving inner peace, resilience, and self-awareness. Findings indicated that cultural and spiritual practices, despite being influenced by migration and economic pressures, retain core beliefs that foster identity and continuity. The study concluded that esoteric attitudes, embedded in daily life and rituals, emphasize humility, gratitude, patience, and sincerity. These values provides a solid foundation for individuals navigating modern existential challenges. By integrating these teachings into everyday life, people can cultivate a deeper sense of purpose and connection, offering valuable insights for contemporary seekers. The research underscores the importance of maintaining and revitalizing traditional spiritual practices to address the complexities of modern existence. Ultimately, the study highlights the timeless relevance of esoteric wisdom in fostering spiritual growth and resilience, helping individuals find balance and meaning amidst the uncertainties of modern life.